Cultural integration of invasive species - Jarić, Ivan; Fernández-Llamazares, Álvaro; Molnár, Zsolt; Arbieu, Ugo; Canavan, Susan; Correia, Ricardo A; Essl, Franz; Kamelamela, Katie L; Ladle, Richard J; Maurice, Anne-Claire; Meinard, Yves; Novoa, Ana; et al. (npj biodiversity, 2025)
Many invasive non-native species gradually become embedded within local cultures. Such species can increasingly be perceived by society as familiar or even native elements of the social-ecological system and become an integral part of local cultures. Here, we explore this phenomenon and refer to it as the cultural integration of invasive species. Although culturally integrated species can positively contribute to people's lives and well-being, and provide new or lost ecosystem services, their acceptance can also hinder the ability of conservation managers to successfully manage invasive species by reducing public support for their management. Cultural integration can infringe upon social values and cultural identities, and contribute to the erosion and homogenization of biocultural diversity. It can also modify or displace the cultural uses and values of native species, and may disrupt social-ecological legacies and dynamics. We present the main mechanisms of cultural integration, its drivers and major implications, and provide key recommendations for the management and conservation of biological and cultural diversity.